Potential of Natural Compounds as Sunscreen Agents - Mansuri, Rani; Diwan, Anupama; Kumar, Harshit; Dangwal, Khashti; Yadav, Dharmender (Pharmacognosy Reviews)
Many skin diseases such as sunburn, pigmentation, wrinkles, dermatitis, urticaria, ageing, skin cancers and immune suppression are due to the extreme exposure to harmful sun radiations. The mere covering of skin through sunglasses, clothes or other external agents is not adequate protection method. Therefore, application of sunscreen is considered as one of the trendiest methods to get rid of the skin aging, sunburn and other related problem arises due to the exposure of ultraviolet radiation (UV) radiations. Sunscreen agents protect from the sun by absorbing the UV and visible sun rays. Herbs have been used in medicines and cosmetics from centuries and their potential to treat different skin diseases, to adorn and improve the skin appearance is well-known. The presented review article is concern with discussion on various plant derived chemicals acting as sunscreen agents such as squalene, peptides, and nucleotides etc and protecting mammalian skin. Herbs and herbal preparations have a high potential due to their antioxidant activity. Antioxidants such as vitamins (Vitamin C, Vitamin E), flavonoids, and phenolic acids play the main role in fighting against free radical species that are the main cause of numerous negative skin changes. Effective botanical antioxidant compounds are widely used in traditional medicine and include tocopherols, flavonoids, phenolic acids, nitrogen containing compounds (indoles, alkaloids, amines, and amino acids), and monoterpenes. Anthocyanin’s, Proanthocyanidin, Quercetin, Anthranilate, Resveratrol, Apigenin, Silymarin, Curcumin, Carotenoids are well known plant derived active chemicals that have potential to absorb radiations. This review covers all essential aspects of potential of herbs as radioprotective agents and its prospects.
Keywords: UV radiation; Skin diseases; Skin Cancer; Photoprotection; Phytochemicals; Herbal products; Sunscreen.